SOSIALISASI METODE PEMBELAJARAN YANG DAPAT MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK USIA DINI KELOMPOK A - Cristiana Normalita de Lima; Mega Suteki; Beatus Tambaip (Fakultas Teknik Universitas Cenderawasih, 2022)
Many parents and teachers do not care about the motor development of early childhood. This is because their paradigm only focuses on certain developments. Therefore, as a professional and good teacher, it is necessary to know what methods need to be used in developing AUD motor skills. This service aims to make AUD teachers know what learning methods can be used in the process of developing children's gross motor skills. This PKM was held at YAPIS Merauke Kindergarten and was attended by 11 YAPIS Merauke Kindergarten teachers. This activity was carried out in 4 sessions where in each session using the lecture method and question and answer discussion. In the end, teachers are expected to be able to create more varied learning methods to support early childhood development.